Poor Efficacy of Immune Checkpoint Inhibitors Plus Chemotherapy in Lung Cancer Patients with EGFR/ERBB2 Exon 20 Insertion. - Zheng, Yue; Fu, Yang; Chen, Yueyun; Li, Qing; Liu, Ting; Ding, Zhenyu (Current Oncology, 2023)
Background: EGFR and ERBB2 exon 20 insertion (Ex20ins) account for a small fraction of patients with EGFR mutations. The efficacy of immune checkpoint inhibitors (ICIs) for these patients was still controversial. Methods: This retrospective study enrolled lung cancer patients harboring either EGFR or ERBB2 Ex20ins mutations. All the patients were treated with platinum-based chemotherapy plus ICIs, or platinum-based chemotherapy. The demographic features and clinical outcome of each patient were reviewed and analyzed. Results: When treated with immunochemotherapy, patients with EGFR/ERBB2 Ex20ins mutations (n = 31) had poor PFS compared with those without EGFR mutations (n = 141, 5.0 mon and 11.2 mon, p < 0.001). When compared with those with EGFR classic mutations who received immunotherapy as the salvage therapy (n = 24), these patients with EGFR/ERBB2 Ex20ins mutations had similar PFS (5.0 mon and 4.1 mon, p = 0.625), ORR (37.5% vs. 48.4%), and DCR (70.8% vs. 77.4%). In the patients with EGFR/ERBB2 Ex20ins mutations, the PFS of those treated with chemotherapy (n = 54) and those treated with immunochemotherapy (n = 31) was 6.5 mon vs. 5.0 mon (p = 0.066). In the EGFR Ex20ins subgroup, the PFS of addition of bevacizumab to chemotherapy (n = 20) and chemotherapy alone (n = 16) was 8.8 mon and 5.2 mon, respectively (p = 0.082) or immunochemotherapy (n = 15, 8.8 mon and 5.0 mon, p = 0.097). Similarly, in the ERBB2 subgroup, the combination of bevacizumab and chemotherapy achieved a numerically longer PFS over chemotherapy alone (9.1 mon and 4.5 mon, p = 0.253), but there was no statistical significance. Conclusions: This study showed that platinum-based chemotherapy plus ICIs had limited efficiency compared to platinum-based chemotherapy for patients with EGFR/ERBB2 Ex20ins. Chemotherapy plus bevacizumab may be a potential scheme for these patients.